Erratum: A genome-wide association study of anorexia nervosa suggests a risk locus implicated in dysregulated leptin signaling - Li, Dong; Chang, Xiao; Connolly, John J.; Tian, Lifeng; Liu, Yichuan; Bhoj, Elizabeth J.; Robinson, Nora; Abrams, Debra; Li, Yun R.; Bradfield, Jonathan P.; Kim, Cecilia E.; Li, Jin; et al. (Scientific reports, 2017)
A correction to this article has been published and is linked from the HTML version of this paper. The error has been fixed in the paper.A correction to this article has been published and is linked from the HTML version of this paper. The error has been fixed in the paper.